DEVELOPMENT OF A SUSTAINABILITY ASSESSMENT TOOL FOR CITIES IN INDONESIA USING THE ANALYTIC HIERARCHY PROCESS METHOD - Anggraini, Rini
In order to measure and assess the sustainability, many developed countries have already developed sustainability assessment tool as a beneficial guidance for planning and policy system for building, neighborhood, and also for cities such as: BREEAM from England, LEED from the US, and CASBEE from Japan. Although these tools have been used in several cities in different countries, the development of the tools are based on the local sustainability issues and developed by local experts and stakeholders of the countries. Indonesia has also developed sustainability assessment tool namely Greenship, but a rating tool to measure and assess sustainability for cities has not been available like other countries Therefore, this research aims to develop Indonesian sustainability assessment tool for cities in accordance with its local context by comparing the main criteria of the international assessment tool and utilizing the Analytic Hierarchy Process Method to obtain the individual judgement from Indonesian experts. The result shows that Indonesian sustainability assessment tool for cities consist of 6 criteria which are further broken down into sub criteria and sub subcriteria. The reliability of the assessment tool is validated by conducting sensitivity analysis. Development of Indonesian sustainability assessment tool for cities can be considered as a starting point for further research of a more comprehensive assessment tool for cities.